A Mixed-method Study of the Effects of Post-migration Economic Stressors on the Mental Health of Recently Resettled Refugees. (November 2021) - Goodkind, Jessica; Ferrera, Julieta; Lardier, David; Hess, Julia Meredith; Greene, R. Neil
After years of emphasis on pre-migration trauma as the major determinant of refugee mental health, researchers have begun to explore the effects of post-migration stressors on refugees' distress. However, few studies have brought together refugees' emic understandings of the effects of economic stressors on their mental health with quantitative data sets to further explore the salience of stress processes as an explanatory mechanism. In qualitative interviews, 41 percent of 290 recently resettled adult refugees noted that economic stressors were a major source of distress and described pathways through which these stressors negatively influenced their mental health by limiting their ability to learn English, obtain meaningful employment, access health care, maintain contact with their families, and integrate into their communities. In structural equation modeling of quantitative data, we tested several possible hypotheses that emerged from the qualitative findings. We find that post-migration economic stressors mediated the relationship between migration-related trauma and post-migration emotional distress and post-traumatic stress disorder (PTSD) symptoms. These findings provide empirical support for stress proliferation as a mechanism through which trauma exposure contributes to distress.